New deep-sea species of Macrostylidae (Asellota: Isopoda: Malacostraca) from the Angola Basin off Namibia, South West Africa - Brandt, Angelika (Zootaxa, 2004)
Six new species of Macrostylidae are described from the deep sea of the Angola Basin off Namibia. These are Macrostylis robusta sp. nov., Macrostylis longipedis sp. nov., Macrostylis angolensis sp. nov., Macrostylis meteorae sp. nov., Macrostylis abyssalis sp. nov., and Macrostylis longispinis sp. nov. The new species are diagnosed, described and illustrated and a revised diagnosis of Macrostylis is presented.